2006
DOI: 10.1007/s11064-006-9199-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential Changes in Phosphorylation of Tau at PHF-1 and 12E8 Epitopes During Brain Ischemia and Reperfusion in Gerbils

Abstract: Cortical neurons are vulnerable to ischemic insult, which may cause cytoskeletal changes and neurodegeneration. Tau is a microtubule-associated protein expressed in neuronal and glial cells. We examined the phosphorylation status of tau protein in the gerbil brain cortex during 5 min ischemia induced by bilateral common carotid artery occlusion followed by reperfusion for 20 min to 7 days. Control brain homogenates contained 63, 65 and 68 kD polypeptides of tau immunoreactive with Alz 50, Tau 14 and Tau 46 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…31 For example, reduced cerebral blood flow in animal models leads to accumulation of amyloid-b oligomers, and increases both neuronal amyloid-b levels and neuronal tau phosphorylation. [32][33][34] Observational studies in humans also suggest an association between CVD risk factors and AD clinical diagnosis, as well as neuropathologic changes of AD. 35 Further supporting the view that ischemia may lead to NFTs in old age, we found that those with high levels of atherosclerosis had more NFTs.…”
Section: Resultsmentioning
confidence: 99%
“…31 For example, reduced cerebral blood flow in animal models leads to accumulation of amyloid-b oligomers, and increases both neuronal amyloid-b levels and neuronal tau phosphorylation. [32][33][34] Observational studies in humans also suggest an association between CVD risk factors and AD clinical diagnosis, as well as neuropathologic changes of AD. 35 Further supporting the view that ischemia may lead to NFTs in old age, we found that those with high levels of atherosclerosis had more NFTs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in AD mice, mild hypoperfusion increases neuronal Ab levels and tau phosphophorylation at an epitotope associated with AD-type paired helical filaments (Koike et al 2010). Brain ischemia in rodents leads to accumulation of hyperphosphorylated tau in neurons and filament formation similar to that present in human AD tauopathy (Gordon-Krajcer et al 2007). Arterial carotid occlusion in rats leads to memory impairment, neuronal dysfunction, synaptic changes and accumulation of neurotoxic Ab oligomers (Wang et al 2010).…”
Section: Cerebral Blood Flow Dysregulation and Reductionsmentioning
confidence: 91%
“…In fact, it was reported that mild hypoperfusion increased neuronal Aβ concentration and the levels of phosphorylated tau in an AD mouse model [76]. It was also observed that brain ischemia in rodent leads to increased levels of hyperphosphorylated tau in neurons and filaments similar to those observed in human AD tauopathy [148]. Moreover, arterial carotid occlusion in rats resulted in neuronal dysfunction, including synaptic changes [149].…”
Section: Reduction Of Capillary Density and Cerebral Blood Flow In Agingmentioning
confidence: 91%